PEMBERDAYAAN MASYARAKAT MELALUI SANGGAR WUNI KREASI DI KUBANGSARON, KOTA CILEGON, BANTEN - Firda Fauziyyah Febriyanah; Sri Mulyanah; Reni Firayanti (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2020)
Sanggar Wuni Kreasi is a Community Activity Center (PKM) which is located in the hamlet of Kubangsaron, Cilegon City, Banten Province. This article aims: 1) to identify the role of Sanggar Wuni as a community organization which is conducted by youths who care about building their own community, 2) to identify sustainability of Sanggar Wuni Kreasi in the empowerment programs, and 3) to analyze the implementation of empowerment programs in the fields of education, arts, crafts, and the Bank Sampah. The research method was carried out with a qualitative approach to obtain relevant data & information in the process of community empowerment activities, especially for rural communities. The results showed that Sanggar Wuni Kreasi was founded due to several complex problems in the community. The existence of Sanggar Wuni Kreasi is interpreted by the community to help increase knowledge, skills, intelligence and entrepreneurship training for people in the hamlet of Kubangsaron. The implementation of programs to empower the community, the presence of Sanggar Wuni Kreasi can reduce the impact of social issues in the Cilegon City that are experienced by the Kubangsaron community, especially young people whose educational levels and unemployment. The target group of the PKM through Sanggar Wuni Kreasi is also reaches residents who are workers at the industrial sectors. The result of this empowerment program is that it can improve the quality of human resources who are competent in their respective fields and have contributed economically to the welfare of the community.